First Identification of Hemolysin (hylA) Gene in Multi Drug Resistant Acinetobacter baumannii Isolated from Clinical Specimens in Iraq - Abdulsadah, Bushra Ghanem; Hadi, Zainab Jaber (Medical Science Journal for Advance Research, 2024)
Background: Acinetobacter baumannii is an extremely problematic bacterium because of its multidrug resistance and fast resistance development capabilities. A. baumannii is widely recognized as one of the most difficult nosocomial pathogens for treatment and control. . Objective:The current study aimed to molecular detection of hylA gene and other virulence genes. Subjects and methods: A study that was cross-sectional was carried out over the course of a period of 5 months, from September 2023 and ending in January 2024. A total of 65 clinical samples were collected from two prestigious institutions, namely Baghdad Teaching Hospital and Al-Sadder Medical City, which are situated in the provinces of Baghdad and Najaf, respectively. In order to guarantee that the diagnosis is accurate, the isolates were subjected to a comprehensive processing procedure that included morphological approaches, biochemical testing, and Vitek2 systems. The susceptibility of antibiotics was evaluated for 22 different antibiotics from 9 antimicrobial categories. Using the disk diffusion method and Colistin Broth Disk Elusion Method used for colistin antibiotic .Monoplex and multiplex conventional PCR analysis used to identify specific virulence genes. Results: The investigation involved the examination of 65 specimens obtained from patients ,which included of sputum 31(47.6%), burn exudate 11(16.9%), wound abscesses 8(12.3%) and blood 7(10.7%), buccal swab 4(6.1%), urine 3(4.6%) , pus 1(1.5%) from the total .The majority of the specimens were collected from hospitalized patients 55 (84.6%) ,while there10 (15.3% ) indicating a substantial contrast in comparison to outpatients . PCR amplification revealed the following genes bla OXA-51 52(80%) ,Omp-A 47(90%) and Bap 19 (37%), FimH 13(25%), FimA(0%) , epsA 19(37%), ptk 11 (21.1%), cnf1 19(37%) , hylA 21(40%) . The rates of resistance were as follows: Ampicillin and Pipracillin(100%),Ampicillin-sulbactam (95%) ,Pipracillin-tazobactam (91%) ,Ticarcillinclavulanicacid (92%), Ceftazidime(95%), Cefotaxime, Ceftriaxone and Cefepime (100%), Imipenem (98%), Meropenem (92%). Amikacin (98%), Gentamicin (91%), Tobramycin (77%), Netilmicin (55%), Doxycycline (40%),Minocycline (20%), Ciprofloxacin(94%), Levofloxacin (92%), Gatifloxacin (28%), Trimethoprim/sulfamethoxazole (92%), Colistin (71%). Conclusions: A higher percentage of A.baumannii isolated from sputum samples. High rates of biofilm formation genes (Omp-A and Bap), Toxin production gene(cnf1)followed by capsular polysaccharide genes (EpsA, ptk), Tissue destruction genes (PlcH, PlcN), Adherence genes (FimH) and FimA was not detected.First reporet of hemolysin gene (hylA) in Iraq.